2019
DOI: 10.1101/669002
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biphasic impact of prenatal inflammation and macrophage depletion on the wiring of neocortical inhibitory circuits

Abstract: The etiology of neurodevelopmental disorders is linked to defects in Parvalbumin (PV)expressing cortical interneurons and to prenatal immune challenges. Mouse models of maternal immune activation (MIA) and microglia deficits increase the postnatal density of PV interneurons, raising the question of their functional integration. Here, we show that MIA and embryonic depletion of macrophages including microglia, have a twostep impact on PV interneurons wiring onto their excitatory target neurons in the barrel cor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 59 publications
(65 reference statements)
2
15
0
Order By: Relevance
“…Abnormal development of synaptic contacts and an altered excitatory versus inhibitory synapse ratio underlie the pathophysiology of these disorders (Braat and Kooy, 2015;Chen et al, 2015a). Consistent with previous findings (Thion et al, 2019), in cortex and striatum, loss of microglial GABA B1 Rs causes a selective increase in inhibitory synapses at P15 and P30 that shifts to a selective decrease at P60. We showed that this change is not microglia-dependent and is therefore likely a compensatory effect.…”
Section: Multiple Lines Of Evidence Support That Gaba-receptive Micro...supporting
confidence: 88%
See 1 more Smart Citation
“…Abnormal development of synaptic contacts and an altered excitatory versus inhibitory synapse ratio underlie the pathophysiology of these disorders (Braat and Kooy, 2015;Chen et al, 2015a). Consistent with previous findings (Thion et al, 2019), in cortex and striatum, loss of microglial GABA B1 Rs causes a selective increase in inhibitory synapses at P15 and P30 that shifts to a selective decrease at P60. We showed that this change is not microglia-dependent and is therefore likely a compensatory effect.…”
Section: Multiple Lines Of Evidence Support That Gaba-receptive Micro...supporting
confidence: 88%
“…An association between microglia and inhibitory synapses has been suggested in the adult and under pathological conditions (Chen et al, 2014;Lui et al, 2016, Liu et al, 2021, the latter of which are often characterized by an aberrant reactivation of developmental programs (Wilton et al, 2019). However, support for this hypothesis has been to date limited to studies in the embryonic brain, where prenatal immune challenges regulate the laminar positioning and connectivity of neocortical parvalbumin (PV) interneurons (Squarzoni et al, 2014;Thion et al, 2019). Here, we demonstrate that GABA-receptive microglia remodel inhibitory but not excitatory synapses during mouse postnatal cortical development.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, MIA in rats has been found to increase the levels of dopamine in both the nucleus accumbens and mPFC ( Luchicchi et al, 2016 ) of offspring, which is well-known to play a role in the positive symptoms of SCZ ( Kesby et al, 2018 ). Additionally, MIA initially triggers hyperinhibition and neuronal miswiring, before leading to a reduced inhibitory drive ( Thion et al, 2019 ). ELS in mice was shown to alter HPA circuity development, in addition to hippocampal and PFC function ( Brenhouse et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, our recordings from adult mice, provides a view on a mature circuitry, which complements evidence that normally focus on animals of younger ages. This is important to consider, since prenatal insults have been shown to lead to age-dependent, biphasic changes in the inhibitory system [64].…”
Section: Discussionmentioning
confidence: 99%